Zaagi’idiwin: Reflections on Love, Indigenous Teaching Practice, and the Hoop Dance Project - Hill, Lauren; John, Beany (Canadian Review of Art Education / Revue canadienne d'éducation artistique)

(untitled) (Canadian Society for Education through Art, 2024)
This paper reflects on an elementary school hoop dance project organized by a white music teacher, taught by an Indigenous hoop dancer, and guided by the Anishinabek goodlife teachings. It suggests that the hoop dance project, and specifically the hoop dancer’s teaching approach, allowed students to experience new, unique, and beneficial learning that engaged the first goodlife teaching: Zaagi’idiwin (love). Furthermore, the experience was a valuable example of Indigenous educational practice, centering relationship and participation. The research argues that current educational realities can impede these best practices and run counter to healthy, holistic and culturally based learning.